A new clinical severity score for the management of acute small bowel obstruction. (28th May 2021) - Wassmer, C -H; Revol, R; Uhe, I; Chevallay, M; Toso, C; Gervaz, P; Morel, P; Ris, F; Schwenter, F; Perneger, T; Meier, R
Abstract: Objective: Small bowel obstruction (SBO) is a common hospital admission diagnosis. Identification of patients who will require a surgical resection because of a non-viable small bowel remains a challenge. We aimed to identify risk factors for intestinal resection in patients with SBO and to develop a practical clinical score designed to guide surgical vs. conservative management. Methods: We performed a prospective cohort study and included all patients admitted for an acute SBO between 2007 and 2016 in our center. Patients were divided in three categories: conservative management, surgical treatment with or without bowel resection. Clinical variables were assessed and compared between groups. Logistic regression models were used to identify the best predictors. Results: 604 patients were included in this study. 438 (73%) had surgery of which 127 (21%) had small bowel resection. 166 (27%) patients were treated conservatively. Among 13 clinical variables, univariate and multivariate logistic regression models identified 8 variables with a strong association with small bowel resection: age ≥70 years, a first episode of SBO, absence of bowel movement for ≥3 days, abdominal guarding, C-reactive protein ≥50, and 3 signs on abdominal CT-scan, namely, small bowel transition point, lack of small bowel contrast enhancement, and the presence of > 500 mL of intra-abdominal fluid. Each variable was given one point. We observed that 71-100% of patients with ≥4 points required a surgical resection. Sensitivity and specificity of this score were 65% and 88%, respectively and the area under the curve (AUC) was 0.84 (95% CI 0.80-0.89). Additionally, we propose two variants of the 8-tem score: a 7-item score excluding the lack of contrast enhancement, specifically designed for patient with contrast allergies or renal insufficiency, and a simplified 4-item score leaving age, guarding, transition zone on CT-scan, and the presence of 500 mL of fluid on CT scan. Both scores showed similar performances compared to the 8-item score with an AUC of 0.83 and 0.80 for the 7- and 4-item scores, respectively. Conclusion: We developed a practical clinical severity score designed to tailor management of patients presenting with a SBO. A score of ≥ 4 points indicates the need for surgical exploration given the high likelihood of small bowel ischemia in these patients.